Analysis of the Effect of Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring on the Performance of Local Government Financial Management in Jambi Province with Human Resource Capacity as a Moderating Variable - Anggun Agustika; Fitrini Mansur; Nela Safelia (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of Government Internal Control System (SPIP) components control environment, risk assessment, control activities, information and communication, and monitoring on the financial management performance of Jambi Provincial Government, as well as to examine human resource capacity as a moderating variable. The study employs a quantitative approach with descriptive and causal research design. A saturated sampling technique was used, involving all 100 employees of BPKPD Jambi Province. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS, preceded by data quality and classical assumption tests. The findings reveal that all SPIP components have a significant effect on financial management performance. The control environment, risk assessment, and control activities show significant negative effects, while information and communication, as well as monitoring, demonstrate significant positive effects. An R² value of 0.834 indicates that the five SPIP variables explain 83.4% of performance variance. Human resource capacity does not moderate most relationships, but negatively moderates the effect of monitoring. This study highlights the crucial role of effective SPIP implementation and continuous human resource development in ensuring strong financial management performance in regional governments.